Long Range Plan For Mental Health Services in California Preliminary Reports of Task Committees - Daniel Blain:::::: (1961)
This 40 page document created by Daniel Blain (Director of Medical Hygiene, is full of reports of the task committees working on the long range plan for mental health services. However these documents do not represent the completed work of the committees but should give a picture of the direction the department in heading, and is asking for suggestions and comments in regards to the this project. To discuss the project the committee met on October 11, 1961 in San Francisco and on October 24, 1961 in Los Angeles. In those sessions the committees the committee used statements on enough evidence to use as a basis for program planning. Those 10 statements, focus on the importance of pregnancy and how the outcome of pregnancy is less favorable in the lower socio economic groups. Factors like nutrition, emotional status, income, and environment have an adverse effect on pregnancy outcome.